2018
DOI: 10.1016/j.ajhg.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Causative Mutations and Mechanism of Androgenetic Hydatidiform Moles

Abstract: Androgenetic complete hydatidiform moles are human pregnancies with no embryos and affect 1 in every 1,400 pregnancies. They have mostly androgenetic monospermic genomes with all the chromosomes originating from a haploid sperm and no maternal chromosomes. Androgenetic complete hydatidiform moles were described in 1977, but how they occur has remained an open question. We identified bi-allelic deleterious mutations in MEI1, TOP6BL/C11orf80, and REC114, with roles in meiotic double-strand breaks formation in wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 54 publications
0
48
0
1
Order By: Relevance
“…(A) The distribution of variants in REC114 exons and the protein structure of REC114. Red arrows indicate new mutations found in our research and the purple arrow indicates the mutation reported previously 22. All variants lie in or around exon 4.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…(A) The distribution of variants in REC114 exons and the protein structure of REC114. Red arrows indicate new mutations found in our research and the purple arrow indicates the mutation reported previously 22. All variants lie in or around exon 4.…”
Section: Resultsmentioning
confidence: 67%
“…Null mutations and overexpression of REC114 both prevent DSB formation in S. cerevisiae , resulting in inviable spores,15 and Rec114 -null mutant mice are defective in both spermatogenesis and oogenesis 14. Recently, Nguyen et al reported that a homozygous splicing mutation in REC114 , which is located directly before exon 4 in the splicing region (purple arrowhead, figure 2A), might cause complete hydatidiform moles (CHMs) in humans, and the patient with the mutation in their paper was reported to have had one miscarriage, two spontaneous CHMs and one CHM after intrauterine sperm injection 22. She had not tried IVF or ICSI technologies, thus the state of fertilisation and embryo development were unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Hydatidiform moles are known to affect approximately 1 in 600 pregnancies, half of which are triploid dispermic (two paternal and one maternal set of chromosomes) and half of which are diploid androgenetic (two paternal sets of chromosomes). An estimated 85% of the latter type are monospermic, and may arise via the extrusion of maternal chromosomes to the first polar body, followed by "diploidization" of the paternal chromosomes (Nguyen et al 2018) . The mosaic near-haploid constitution of embryo E7.5 is theoretically consistent with a dispermic origin, as a result of postzygotic diploidization of a triploid zygote (Golubovsky 2003) .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of androgenetic CHM development, and maternal nucleus loss, has been known for a long time. Recently, MEI1, TOP6BL/ C11orf80, and REC114 were reported as candidate causative genes by screening patients with recurrent androgenetic CHMs 24 . In Mei1-deficient female mice, 8% of the oocytes lose all their chromosomes by extruding them with the spindles into the first polar body.…”
Section: Discussionmentioning
confidence: 99%